2009
DOI: 10.1897/08-341.1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle characteristics affecting environmental fate and transport through soil

Abstract: Nanoparticles are being used in broad range of applications; therefore, these materials probably will enter the environment during their life cycle. The objective of the present study is to identify changes in properties of nanoparticles released into the environment with a case study on aluminum nanoparticles. Aluminum nanoparticles commonly are used in energetic formulations and may be released into the environment during their handling and use. To evaluate the transport of aluminum nanoparticles, it is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
155
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(156 citation statements)
references
References 33 publications
0
155
0
1
Order By: Relevance
“…Positively charged Al 2 O 3 NPs (50,80, and 120 nm) demonstrated relatively low mobility [74] because of sorption to negatively charged soil surfaces. Conversely, Al 2 O 3 NPs (50 nm) with adsorbed phosphate, producing a net negative charge, showed reduced sorption to soil and hence higher mobility [73]. A similar effect of phosphate on CeO 2 NPs has also been noted [56].…”
Section: Transport Of Metal-based Nps In Soilmentioning
confidence: 61%
See 2 more Smart Citations
“…Positively charged Al 2 O 3 NPs (50,80, and 120 nm) demonstrated relatively low mobility [74] because of sorption to negatively charged soil surfaces. Conversely, Al 2 O 3 NPs (50 nm) with adsorbed phosphate, producing a net negative charge, showed reduced sorption to soil and hence higher mobility [73]. A similar effect of phosphate on CeO 2 NPs has also been noted [56].…”
Section: Transport Of Metal-based Nps In Soilmentioning
confidence: 61%
“…The interaction occurring between particles and solid surfaces will control the transport of NPs through soils [73]. This interaction may be influenced by both environmental conditions and the physicochemical characteristics of the particles (Fig.…”
Section: Transport Of Metal-based Nps In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size of alkaline soil is higher (>4 mm diameter) than in the case of non-alkaline soil (2 mm diameter) (Barral et al 1998;van der Wal et al 2007). The pore size of soil matrix may increase the effect of filtration which result the main elemental concentration between alkaline and non-alkaline soil (Darlington et al 2009). We used PI to assess the pollution level of soils in Wien.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is also well known for traditional chemicals, some challenges relate specifically to ENMs. Natural soils represent a large and reactive sink, and recent studies have shown that natural soil will filter ENMs during transport through the soil matrix, particularly if the clay content or ionic strength is elevated [75][76][77]. Likely the bioavailability of ENMs to soil organisms, as for aquatic sedimentary tests, will differ for natural and artificial soils, and the method of dosing the soil will alter this bioavailability.…”
Section: Behavior Of Enms In the Soil Matrixmentioning
confidence: 99%